Detection of Aerobic Vaginitis and Antibiogram of its Implicating Bacteria among Women with Suspected Cases of Vaginitis in Obstetrics and Gynecology Clinics, Ahmadu Bello University Teaching Hospital, Shika, Zaria-Nigeria - Bashir Abdullahi; Maryam Aderonke Bello (UMYU Journal of Microbiology Research)
Aerobic vaginitis (AV) is a condition caused by aerobic bacteria, posing significant risks to women's health, particularly during pregnancy. Misdiagnosis and treatment challenges stem from widespread multidrug-resistant bacteria. This study aimed to diagnose aerobic vaginitis (AV) and assess antibiotic susceptibility patterns of the implicated bacteria in vaginitis among women attending Ahmadu Bello University Teaching Hospital's Obstetrics and Gynecology Clinics in Zaria, Nigeria. A total of 100 high vaginal swab (HVS) samples were collected and subjected to bacterial isolation, identification, and antibiotic susceptibility testing using cultural and biochemical methods, and the agar disc diffusion method, respectively. Results indicated 23% positivity for AV, with the highest prevalence observed in the 41-50 age group (50.0%) and the lowest in the 21-30 age group (7.3%), revealing a significant association between age and AV (p<0.05). While third-trimester pregnant women displayed a higher AV rate (32.0%) than those in their second trimester (0%), no significant association was found between gestational periods and AV (p>0.05). Symptomatically, painful intercourse correlated with a 28.0% AV rate, while vaginal itching showed an 18.5% rate, though lacking a symptom-AV relationship (p>0.05). Notably, condom use during sexual intercourse exhibited a higher AV rate (63.6%) than non-users (18.0%). AV prevalence was notably higher among women with a history of miscarriage (62.5%) compared to those without (15.5%), showing a significant association between risk factors and AV (p<0.05). Klebsiella species (47.8%) and Escherichia coli (30.4%) were the primary AV-associated bacteria, with Klebsiella spp. showing high resistance to Ceftriaxone and Ampicillin (100%). These findings underscore the importance of accurate AV diagnosis to avert adverse outcomes like miscarriage and postpartum complications and highlight the need to reconsider Ceftriaxone and Ampicillin usage in AV treatment.